2010
DOI: 10.2490/jjrmc.47.239
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rehabilitation for Patients with HAM (HTLV-1 associated myelopathy)

Abstract: The effectiveness of rehabilitation in patients with HTLV-1 associated myelopathy HAM was evaluated. The HAM patient is characterized by chronic progressive spastic paraplegia with dysuria and muscular weakness of the lower trunk, as well as the pelvic and hip muscles. However, the muscular strength of the lower limbs and feet is relatively well maintained. The 12 subjects enrolled in this study included 2 men and 10 women. Their average age was 53.2 years, their average duration of disease was 20.5 years, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Further studies are needed to clarify the association between HTLV-1 and muscle disease. Even without concomitant muscular disease, past studies have shown that patients with HAM/TSP have proximal muscle weakness [11][12][13]25,26], and magnetic resonance imaging studies suggest the same [27]. In patients with hereditary spastic paraparesis unrelated to HTLV-1 infection, proximal muscle weakness is not common [28], whereas, in patients with bulbospinal muscular atrophy and some hereditary peripheral neuropathies, proximal muscle weakness is even a hallmark of the disease [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to clarify the association between HTLV-1 and muscle disease. Even without concomitant muscular disease, past studies have shown that patients with HAM/TSP have proximal muscle weakness [11][12][13]25,26], and magnetic resonance imaging studies suggest the same [27]. In patients with hereditary spastic paraparesis unrelated to HTLV-1 infection, proximal muscle weakness is not common [28], whereas, in patients with bulbospinal muscular atrophy and some hereditary peripheral neuropathies, proximal muscle weakness is even a hallmark of the disease [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions are symmetrically distributed mainly in the lateral column and to a lesser extent in the inner portion of the posterior columns; they are also present in the central gray matter [9,10]. Takezawa et al [26] performed a study of rehabilitation for muscle weakness of the trunk and proximal muscles of the lower extremities and reported that the weakness in patients with HAM/TSP can be explained at the level of the spinal cord segments, given that the innervation of the erector spinae muscles is distributed in the lower thoracic segments with trunk extensors from Th6 to Th11 and trunk flexors from Th7 to Th11. However, patients with HAM/TSP usually have stronger hip adductor muscles (L2-4) and weaker hip abductor muscles (L5S1), and the present study also confirms that the abductor muscle group is weaker than the adductor muscle group, suggesting that there are factors other than spinal segmental level.…”
Section: Discussionmentioning
confidence: 99%